The Efficacy of the Integrated Health Service Post Cadres Training in Noncommunicable Disease Prevention Among Older People in Southwest Papua - Samaran, Elisabeth; mustamu, Alva Cherry; Mamo, Yoseph (Universitas Nahdlatul Ulama Surabaya, 2025)
causes of morbidity and mortality globally, with a significant impact on older people, particularly in regions with limited healthcare access, such as Southwest Papua. Community-based approaches, such as the Integrated Health Service Post program, potentially enhance the early detection and prevention of NCDs. However, the implementation still faces several challenges. This study evaluates the efficacy of the Integrated Health Service Post cadres training in improving the early detection and prevention of NCDs and healthy lifestyle changes among older people in Southwest Papua. It used a quasi-experimental design with a prospective approach involving 150 older people from six congregations of the Indonesian Protestant Church in Southwest Papua. The intervention comprised cadres training based on a structured module for the early detection and prevention of NCDs, followed by implementing the Integrated Health Service Post over six months. Data were collected using validated instruments and analyzed using statistical software. The results demonstrated a statistically significant improvement in the early detection of NCDs in the intervention group compared to that in the control group (p<0.001). In addition, there are more significant improvements in physical activity and healthy eating habits and the reduction of NCD risk factors in the intervention group compared to the control group. Cadres' adherence to the Standard Operating Procedures (SOP) of the Integrated Health Service Post was also high. In conclusion, empowering health cadres through community-based training significantly improves preventive health outcomes among older people in areas with limited healthcare access. KEYWORDSCommunity-Based Program, Integrated Health Service